The use of ozone therapy in the treatment of diabetic foot: integrative review (Research, Society and Development, 2020)
Diabetes Mellitus is considered a public health problem because it is a disease with high morbidity and mortality and incapacitating due to its complications. Ulcerations are frequent on the feet of people with diabetes, with infection being the main factor involved in the sequence of events that often lead to lower limb amputation and readmissions. Ozone is an alternative adjuvant treatment for difficult-to-heal lesions such as ulcers caused by diabetes. The objective is to evaluate the scientific evidence, in national and international literature, on the use of ozone therapy as a treatment for patients with diabetic foot. This is an integrative review with eight articles selected from the Virtual Health and Scielo databases between 2010 and 2020. After reading, analyzing and interpreting the data, it can be seen that, although there are few studies recent on ozone therapy in the treatment of diabetic foot, the articles elucidate the use of ozone as a promising treatment modality, which reduces the healing time and improves the appearance of injuries. However, not all studies show the time of application and the route of treatment. There is a need for further research to create standards or protocols in order to optimize the quality of care for patients with diabetic foot.